Angiogenic Imbalance and Residual Myocardial Injury in Recovered Peripartum Cardiomyopathy Patients. (November 2016) - Goland, Sorel; Weinstein, Jean Marc; Zalik, Adi; Kuperstein, Rafael; Zilberman, Liaz; Shimoni, Sara; Arad, Michael; Ben Gal, Tuvia; George, Jacob
Abstract : Background—: Recent studies suggest that angiogenic imbalance during pregnancy may lead to acute peripartum cardiomyopathy (PPCM). We propose that angiogenic imbalance and residual cardiac dysfunction may exist even after recovery from PPCM. Methods and Results—: Twenty-nine women at least 12 months after presentation with PPCM, who exhibited recovery of left ventricular (LV) ejection fraction (≥50%), were included in the study (mean age 35±6 years, LV ejection fraction 61.0±3.9%). The number of circulating endothelial progenitor cells (EPCs) and plasma levels of proangiogenic vascular endothelial growth factor and of soluble vascular endothelial growth factor receptor Flt1 (sFlt1) were measured. All patients underwent comprehensive cardiac function assessment, including tissue Doppler imaging and 2-dimensional (2D) strain echocardiography. All measurements were compared with healthy controls. Patients with a history of PPCM have significantly higher sFlt1 concentrations (median [25th–75th percentile]; 149.57, [63.14–177.89] versus 20.29, [15.00–53.89] pg/mL, P <0.001) and significantly decreased vascular endothelial growth factor/sFlt1 ratio ( P =0.012) compared with controls, with a trend toward lower concentration of circulating CD34 + /KDR + levels. In addition, patients with PPCM had lower early velocities E′ septal (9.9±2.1 versus 11.0±1.5 cm/s, P =0.02), with a significantly lower systolic velocity S′ septal (7.6±1.2 versus 8.5±1.2 cm/s, P =0.003) by tissue Doppler imaging. Significantly lower LV global longitudinal (−19.1±3.3 versus −22.7±2.2%, P <0.001) and apical circumferential 2D strain (−16.6±4.9 versus −21.2±7.9, P =0.02) were present in patients with PPCM compared with controls. Conclusions—: Higher concentration of sFlt1 with concomitant decreased circulating endothelial progenitor cell levels along with inappropriate attenuated vascular endothelial growth factor levels may imply an angiogenic imbalance that exists even after recovery and may thus predispose to PPCM. In addition, tissue Doppler imaging and 2D strain were able to identify residual myocardial injury in post-PPCM women with apparent recovery of LV systolic function. Both angiogenic imbalance and residual myocardial injury may play an important role in the recurrence of LV dysfunction during subsequent pregnancies.